Pengembangan Modul Ajar Berbasis Terdiferensiasi dalam Materi Bangun Ruang Sisi Lengkung (Fase D) pada Siswa SMP Negeri 6 Sungai Kakap - Puspita, Ela; Haryadi, Rahman; Darma, Yudi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to develop learning media in the form of differentiated-based teaching modules in the material of curved side space (phase D). This study uses the ADDIE development model with the following procedures: Analysis, Design, Development, Implementation, and Evaluation. This study was conducted at SMP Negeri 6 Sungai Kakap, Kubu Raya Regency. Data collection techniques used in this study were indirect communication techniques, measurement techniques, direct communication techniques, documentation, and observation. While the data collection tools used were expert validation sheets, response questionnaires, and problem-solving ability test sheets. The data analysis technique used was to find the validity, practicality, and effectiveness of the teaching module. The level of validity with a very valid category with media validity of 86.59% and material 83.44%. The level of practicality with very practical criteria is indicated by the student response questionnaire reaching a value of 96.05% and the teacher response questionnaire 92%. The level of effectiveness with effective criteria based on the completion value determined by the school. The test results showed an effectiveness index of 0.6389 with the criteria of